Cytosolic delivery of large proteins using nanoparticle-stabilized nanocapsules. Issue 42 (14th October 2016) - Tang, Rui; Jiang, Ziwen; Ray, Moumita; Hou, Singyuk; Rotello, Vincent M.
Abstract : We report an effective intracellular delivery strategy for proteins of high molecular weight using AuNP stabilized capsules. Abstract : We report an effective intracellular delivery strategy for proteins of high molecular weight using AuNP stabilized capsules. This strategy provides direct delivery to the cytosol, avoiding endosomal entrapment.